Adults with previous hypospadias surgery during childhood: Beware of bulbar strictures. Issue 1 (February 2022) - Faraj, Sebastien; Loubersac, Thomas; Bouchot, Olivier; Heloury, Yves; Leclair, Marc-David
Summary: Background: Urethral strictures represent the most frequent long-term complication in men after history of hypospadias surgery. Objectives: To better define the spectrum of men previously treated for hypospadias during childhood, presenting at an adult urology clinic with persistent urethral complications. Study design: Retrospective review of the records of 42 consecutive adult patients with a personal history of hypospadias repair during childhood referred at one adult tertiary urology center between 2004 and 2017. Those with persistent urethral strictures were included: 28 patients (median age 28yr [17–81]). Residual chordee, aesthetic concerns, isolated fistulas, and motives of consultation unrelated to hypospadias were excluded. Early initial success rate and location of urethral stricture were studied. Statistical Analysis was done by non-parametric tests. Results: On the 42 consecutive adults eligible, a total of 28 patients had a persistent urethral stricture. During childhood, 13/28 boys had required multiple surgical revision procedures, including six of them for postoperative urethral strictures. During adulthood, initial urethral assessment revealed 29 urethral strictures in 28 patients (penile urethra 23/29, bulbar urethra 8/29). The early initial success rate of stricture treatment was 50% (median follow-up: 4 years [1–7]). Additional surgical procedures were needed and performed in 11 patients. Eight patients were eventually diagnosed with a bulbar stricture, either isolated (n = 5) or combined with a distal stricture (n = 3), without significant relationship with initial position of meatus. Discussion: Predictive factors for bulbar strictures locations could not be identified. It was however observed that symptomatic bulbar strictures do exist in adults, in the long term after penile hypospadias repair during childhood, independently of the initial site of hypospadias, initial success of primary repair, and the type of surgical reconstructions performed during childhood. Conclusion: Bulbar strictures represent more than 25% of the overall strictures diagnosed in adult patients treated for hypospadias during childhood, independently of the original site of urethral reconstruction. Summary Table Characteristics of patients according to stricture location. Summary Table DISTAL Stricture only BULBAR Stricture p = n= 20 8 Initial position of meatus Anterior 10 6 0.48 Penile 8 2 0, 94 Posterior 2 0 0, 7 Hypospadias first repair MAGPI 0 1 0, 57 TIP 7 2 0, 77 Mathieu 5 2 1 Onlay 0 1 1 Duckett 6 2 1 Cecil-Leveuf 2 0 0, 98 Late initial surgery (>3 years) 4 0 0, 38 Staged primary surgery 3 0 0, 7 Childhood complications after initial surgery None 13 4 0, 26 Stenosis 3 3 0, 32 Fistula 4 0 0, 28 Dehiscence 1 1 1 Other interventions during childhood None 9 2 0, 61 Non-urethral redo-surgery 3 1 1 Redo-urethroplasty and multiple surgeries 8 5 0, 46 MAGPI: Meatal Advancement and GlanuloPlasty Intervention. TIP: Tubularized Incised Plate.